Fundamentals of convective heat transfer - Biswas, G.; Dalal, Amaresh; Dhir, V. K. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
Thermal convection is often encountered by scientists and engineers while designing or analyzing flows involving exchange of energy. Fundamentals of Convective Heat Transfer is a unified text that captures the physical insight into convective heat transfer and thorough, analytical, and numerical treatments. It also focuses on the latest developments in the theory of convective energy and mass transport. Aimed at graduates, senior undergraduates, and engineers involved in research and development activities, the book provides new material on boiling, including nuances of physical processes. In all the derivations, step-by-step and systematic approaches have been followed.
3.6 SUMMARY OF SOLUTIONS FOR VARIOUS FLOW AND HEAT TRANSFER SITUATIONS IN PIPE FLOWS3.7 HEAT TRANSFER IN COUETTE FLOW; 3.8 CONVECTION CORRELATIONS FOR NON-CIRCULAR TUBES; CHAPTER 4: Solution of Complete Navier-Stokes and Energy Equations for Incompressible Internal Flows; 4.1 INTRODUCTION; 4.2 SOLUTION OF NAVIER STOKES EQUATIONS IN CARTESIAN COORDINATE; 4.2.1 Staggered Grid; 4.2.2 Introduction to MAC method; 4.3 SOLUTION OF ENERGY EQUATION IN CARTESIAN COORDINATE; 4.3.1 Solution Procedure; 4.3.2 Flow Chart; CHAPTER 5: Fluid Flow Solutions in Complex Geometry; 5.1 INTRODUCTION
OCLC-licensed vendor bibliographic record.
Keywords: Heat -- Transmission; SCIENCE / Mechanics / Dynamics / Thermodynamics; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Engineering / Mechanical